The importance of scientific competencies in German medical curricula - the student perspective - Ratte, Antonius; Drees, Simon; Schmidt-Ott, Tabea (BMC medical education, 2018)
Scientific competencies are of great importance for physicians; not only for conducting reliable research, but also for patient care. However, there is growing concern that a lack of scientific competencies among physicians may lead to a deterioration in the quality on biomedical research. This study aims at assessing medical students’ perspectives on the implementation of scientific competency training in German medical curricula.